1999
DOI: 10.1021/ac980952b
|View full text |Cite
|
Sign up to set email alerts
|

An Ion-Selective Electrode for Acetate Based on a Urea-Functionalized Porphyrin as a Hydrogen-Bonding Ionophore

Abstract: An ion-selective electrode for acetate based on (α,α,α,α)-5,10,15,20-tetrakis[2-(4-fluorophenylureylene)phenyl]porphyrin as an ionophore that has no metal center and forms hydrogen bonds to the analyte is described. At pH 7.0 (0.1 M HEPES-NaOH buffer), the electrode based on this ionophore and cationic sites (50 mol % relative to the ionophore) responds to acetate in a linear range from 1.58 × 10(-)(4) to 1.58 × 10(-)(2) M with a slope of -54.8 ± 0.8 mV/decade and a detection limit of (3.06 ± 1.15) × 10(-)(5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 54 publications
2
45
2
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12] Thus, we used an experimental kit having a porous membrane filter, which was infiltrated with the solvent mediator.…”
Section: Several Solvent Mediators (Such As Ooo-tris(2-ethylhexyl) mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11][12] Thus, we used an experimental kit having a porous membrane filter, which was infiltrated with the solvent mediator.…”
Section: Several Solvent Mediators (Such As Ooo-tris(2-ethylhexyl) mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Typical examples are the use of hydrogen-bonding ionophores with urea or thiourea units, which were successfully used to produce anion-selective electrodes, including those to nucleotides, Cl -, SO4 2-and acetate. [2][3][4][5] Hydrogen-bonding solvent mediators, such as tris (2-ethylhexyl) phosphate and tricresyl phosphate, have also been used to construct organic ammonium ion-selective electrodes, [8][9][10][11] through the interaction between NH3 + groups of organic ammonium ions and the negatively polarized oxygen atoms in the P=O groups of phosphate esters. 7 In the process of screening various phosphate and thiophosphate esters, we found that prothiofos ((O-(2,4-dichlorophenyl) O-ethyl S-propyl phosphorodithioate, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…34 Table 4 lists the linear range, detection limit, slope, response time and selectivity coefficients of some of other thiocyanateselective electrodes against the proposed thiocyanate-selective electrode for comparative purposes. 25,[35][36][37][38] As can be seen from the table, the selectivity coefficients obtained for the proposed electrode are superior to those reported for other SCN --selective electrodes listed in Table 4.…”
Section: Selectivity Of the Electrodementioning
confidence: 60%
“…ISEs are also of obvious interest because they can help translate the chemistry of new substrate binding systems into tools that can be used to recognize selectively various targeted species in the presence of potentially interfering analytes. In the specific case of anion recognition, this approach has been explored extensively by Umezawa, Meyerhoff, Simon, Reinhoudt, Schmidtchen and others using a range of receptors including bis-guanidinium [1][2], porphyrins [3], protonated polyamines [4][5][6][7], and protonated sapphyrins [8][9][10], as well as a variety of Lewis acidic systems such as calixarenes [11][12][13][14][15], uranylsalenophenes [16][17], metalloporphyrins [18][19][20][21][22], metallocenes [23], other organometallic derivatives [24][25][26], and fluorinated compounds [27].…”
Section: Introductionmentioning
confidence: 99%